Intention of Collaboration among Dental Students during the COVID-19 Pandemic - Kyriaki Hadjichambi; Evie Georgiadou; Vasileios Margaritis; Maria Antoniadou (MDPI AG, 2022)
Interpersonal communication skills (ICS) are crucial for effective dental practice and interprofessional collaboration. The current study aimed to assess the attitudes of Greek dental undergraduate students towards team working and their cooperation abilities during the COVID-19 pandemic. One-hundred and twenty-seven fourth-semester dental students (N1 = 127) out of 145 (N0) filled in the online survey placed on Google forms. The "Dental Students Cooperation Questionnaire" (DSC) consisted of 49 questions and was available for completion for one week during April 2020. Bivariate (ANOVA) and linear regression analysis of data revealed that mean scores of the questionnaire increased as the parents' educational level also increased. Data analysis showed that dental students had the required ICS and the intention to collaborate with each other. Many participants managed to achieve group goals, were willing to support other members to fulfill the project's goals, and there was no competition among them. They acknowledged the importance of feedback, the reward at the end of a group project and social media as a tool for teamworking communication. The students reported that the most important characteristics of an academic teacher were patience, willingness to cooperate, friendliness, politeness, willingness to help, accessibility and availability. It is suggested that group work should be included in the curriculum of dental schools to enhance the integration and evolution of students' ICS, and the DSC questionnaire can be an effective tool to assess these skills.